Crowdsourcing human mutations (Nature genetics, 2011)
The first Human Variome microattribution review shows that data citation and publication credit can work as incentives for systematic curation of gene variant and phenotype data. Analysis of the formal assertions in both databases and journal articles argues for better separation of data structures from narrative so that they can better support one another to communicate meaning.